(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Medicinal plants are an excellent source as they provide a wide variety of possible therapeutic compounds that are both diversified and reasonably safe, compared to manufactured pharmaceuticals. In the current study we aimed to evaluate the qualitative and quantitative phytochemical analysis of drumstick parts of Moringa oleifera plant. The aqueous (aq.) extract of drumstick parts of Moringa oleifera plant was prepared by maceration of 100 g of sample powder of drumstick parts of M. oleifera in two liters of distilled water was macerated for 24 hours followed by filtration using Whatman filter paper No.1. The qualitative and quantitative phytochemical analysis was carried for aq. drumstick extract of M. oleifera. Qualitative phytochemical analysis of aq. drumstick extract of M. oleifera revealed alkaloids, flavonoids, sterols, and tannins as major phytochemicals found in aq. drumstick extract of M. oleifera. Quantitative phytochemicals estimation of aq. drumstick extract of M. oleifera revealed that tannins were found to be present in highest quantities i.e., 24.89 ± 2.41% followed by flavonoids, sterols, and alkaloids in 6.15 ± 0.28%, 5.04 ± 0.15%, and 3.65 ± 0.16% respectively. In conclusion, study findings clearly demonstrated that aq. drumstick extract of M. oleifera contains secondary metabolites viz. alkaloids, flavonoids, sterols, and tannins that are beneficial in treatment of various human ailments. Hence, Moringa drumsticks could be explored in the traditional medicine as antipyretic, antioxidant, analgesic agents, immune enhancers, and hormone modulators.